2022
DOI: 10.5812/amh-128009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of a Natural Formulation Based on Hordeum Vulgare on the Recovery of COVID-19 Patients: Application of Survival Analysis in a Clinical Trial

Abstract: Background: Coronavirus disease 2019 (COVID-19) has affected the lives of people all over the world. Although researchers are working to manage and minimize the impact of the current COVID-19 pandemic, no definitive treatment method has been identified so far. The present clinical trial aimed to evaluate the survival of two groups of patients with COVID-19. Methods: The statistical population of this prospective clinical trial included 70 patients hospitalized in the Mofatteh Hospital in Varamin, Iran, from 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Previous studies showed the positive effect of venesection in the treatment of vertigo, dizziness, carpal tunnel syndrome, musculoskeletal disease, sciatica, and non-specific pains of the back, neck, and arms. The most commonly reported benefit of this technique is pain relief 12 , 23 25 . Amini et al 12 hypothesized that venesection would alleviate the pain, thus improving the quality of life in patients with sciatica.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed the positive effect of venesection in the treatment of vertigo, dizziness, carpal tunnel syndrome, musculoskeletal disease, sciatica, and non-specific pains of the back, neck, and arms. The most commonly reported benefit of this technique is pain relief 12 , 23 25 . Amini et al 12 hypothesized that venesection would alleviate the pain, thus improving the quality of life in patients with sciatica.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported benefit of this technique is pain relief 12 , 23 25 . Amini et al 12 hypothesized that venesection would alleviate the pain, thus improving the quality of life in patients with sciatica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiviral activity is also shown by Artemisia annua which is one of the ingredients of Reduning Injection. Artemisia annua can inhibit SARS-CoV-2 attachment, membrane fusion and internalization into host cells, and reduce viral replication and transcription processes ( Amini et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral activity is also shown by Artemisia annua which is one of the ingredients of Reduning Injection. Artemisia annua can inhibit SARS-CoV-2 attachment, membrane fusion and internalization into host cells, and reduce viral replication and transcription processes (Amini et al, 2022). Molecular docking analyses showed that the components present in Reduning Injection possess the capability to spontaneously bind to papain-like protease (PLpro), Mpro, and angiotensin-converting enzyme-2 (ACE-2).…”
Section: Antiviralmentioning
confidence: 99%